Preliminary study on the potential of topical anaesthesia from betel leaf and clove leaf extract - Ronal, Ahmad; Astuti, Fadhilah Nadya; Pratiwi, Lintang; Prihastari, Lisa (Universitas Padjadjaran, 2021)
Introduction: Betel leaf (Piper betle Linn.) and clove leaf (Syzygium aromaticum) are Indonesian herbs which are known to cause a numb sensation. The main ingredients of betel leaf, which act as an anesthetic, are caryophyllene, eugenol, methyl eugenol, eucalyptol (1.8-cineol), linalool, α-Pinene, estragole, while cloves have local anesthetic effects through their ingredients, namely eugenol, and β-Caryophyllene. Research on the benefits of these two ingredients as topical anesthetics in Indonesia is still rare. This study was aimed to describe the potential of betel leaf and clove leaf extract as a topical anesthetic in Wistar rats. Methods: This research was a laboratory experimental research with simple randomized controlled design. The sample consisted of 6 male Wistar rats, each of which was given four treatments, namely extract with a concentration of 50%, 75%, and 100%, and topical anaesthetic benzocaine 20% as a control. Each treatment was tested using an electric stimulator and observed onset, duration of action, and depth of topical anaesthesia. The data were processed using descriptive statistics with tables and graphs. Results: Betel leaf extract with a concentration of 100% had a better mean onset, duration of work, and depth of anesthesia than the 20% benzocaine control, whereas 75% clove leaf extract had the longest duration of action compared to 20% benzocaine and 100% concentration was the topical anesthetic agent with the highest anesthetic depth. Conclusion: Based on the onset, duration of action, and depth of anesthesia, betel leaf, and clove leaf have potential as topical anesthetic agents.